Expression of cardiac angiotensin-converting enzyme after myocardial infarction - Zhu Yi-chun; Falkenhahn Mechthilt; Franke Folker; Bohle Rainer Maria; Stauss Harald Martin; Danilov Sergei; Unger Thomas (Acta Pharmacologica Sinica, 2016)
AIM: To localize cardiac angiotensin-converting enzyme (ACE) during left ventricular repair after myocardial infarction (MI). METHODS: Cardiac ACE was examined by immunohistochemical staining using monoclonal and polyclonal antibodies against ACE 24 h, 1 wk, 2 wk, 3 wk, and 6 wk after coronary artery ligation in rats. Immunofluorescent double staining technique was applied to distinguish the cells which express ACE. RESULTS: ACE staining was confined to the endothelial cells and distributed in normal cardiac tissue in a gradient pattern along the vascular tree: present around the whole circle of arterial endothelium, present in about 20% of the capillaries, and absent in the veins. One week after MI, ACE expression was noted in the granulation tissue. Three weeks after MI, necrosis within the infarction was replaced by granulation tissue and fibrous tissue which showed strong over-expression of ACE. Six weeks after MI, the region with positive ACE staining regressed and the area with high collagen content on the endocardial side showed only weak ACE stain. Most of the ACE-positive cells in the ACE-over-expression-area were endothelial cells. A few macrophages seen in these regions were also ACE-positive. CONCLUSION: Cardiac ACE was over expressed during the process of tissue repair following MI, reaching a peak in 3 wk. Endothelial cells took the most part of ACE expression.